Creep Rupture Behavior in Dissimilar Weldment between FB2 and 30Cr1Mo1V Heat-Resistant Steel - Jiankun Xiong; Jianping Yang; Haiyan Zhao; Lin Yang; Yang Guo; Fuheng Nie; Dexing Xu; Liping Yu; Fenghong Cao (International Journal of Photoenergy)
Creep rupture behavior of dissimilar weldments between FB2 and 30Cr1Mo1V heat-resistant steel by multipass welding at 783 K (510°C) under different stresses (260 to 420 MPa) was researched. The fitted creep rupture exponent is 14.53, and the 10,000 h extrapolating strength values predicted by the power law and Larson-Miller parameter show good agreement with experimental data. The samples exhibit a ductile fracture character and fracture in the weld fusion zone, which has a highly heterogeneous microstructure and grains with different morphologies and sizes and an obvious softening. There exist a decrease in the dislocation and precipitate density and an increase in the subgrain size in the weld metal after creep. The rupture is a transgranular fracture characterized by dimples as a result of microvoid coalescence. Laves phases along with copper-rich precipitates are observed in the vicinity of fracture surface, which creates a stress concentration that can cause transgranular fracture initiation.